'Things of the sea': iconographic continuities between tattooing and handicrafts in Georgian-era maritime culture. (2015) - Lodder, Matt
Abstract : The National Maritime Museum in Greenwich owns a 1941 portrait bust by Charles Thomas Wheeler of Captain George Elvey Creasy, the Director of Anti-Submarine Warfare and later Admiral of the Fleet. On the nape of his neck, carved into the bronze, is the depiction of a tattoo: a merman fighting a dragon covered in Nazi swastikas. From an account of this object, this article argues that, though this depiction of tattooing in formal sculpture is extraordinarily rare, there is a remarkable continuity between maritime tattooing and the iconographic lexicon of images in informally produced handicrafts made by sailors at sea. The incised tattoo in Wheeler's sculpture of Creasy mimics not only ink inserted into the skin, but also the engraved, scored and carved marks made by sailors into their mess-tins and other items over several centuries. With particular focus on the context of the wider visual culture of the Georgian fleets, this article argues that early Euro-American maritime tattooing can only be understood in relation to the broader visual culture from which it emerges. Rather than being an esoteric practice, tattooing in the late eighteenth- and early nineteenth-century fleets is best understood as part of a broader set of craft and folk art practices with which tattooing overlaps both iconographically and technologically. Moreover, the comparison between tattooing and several maritime handicrafts – particularly the engraving of objects such as tobacco tins and love tokens – offers a rich and nuanced set of methodologies for thinking about tattooing as a visual art practice.